Carbonatite complexes of the South Urals: geochemical features, ore mineralization, and geodynamic settings - Irina L. Nedosekova (Записки Горного института, 2022)
The article presents the results of study of the Ilmeno-Vishnevogorsky and Buldym carbonatite complexes in the Urals. It has been established that the carbonatites of the Ilmeno-Vishnevogorsky complex are represented by high-temperature calciocarbonatites (sövites I and II) with pyrochlore ore mineralization. U-Ta-rich populations of uranium pyrochlores (I) and fluorocalciopyrochlores (II) crystallize in miaskite-pegmatites and sövites I; fluorocalciopyrochlores (III) and Sr-REE-pyrochlores (IV) of late populations form in sövites II. In the Buldym complex, along with high-temperature calciocarbonatites containing fluorocalciopyrochlore (III), medium-temperature varieties of magnesiocarbonatites with REE-Nb mineralization (monazite, niobo-aeschynite, columbite, etc.) are widespread. Miaskites and carbonatites of the Urals are characterized by high contents of LILE (Sr, Ba, K, Rb) and HFSE (Nb, Ta, Zr, Hf, Ti), which are close to the contents in rift-related carbonatite complexes of intraplate settings and significantly differ from synorogenic collisional carbonatite complexes. The Ural carbonatite complexes formed on continental rift margins during the opening of the Ural Ocean at the time of transition from extensional to compressional tectonics. Later on, they were captured and deformed in the suture zone as a result of collision. Plastic and brittle deformations, anatexis, recrystallization of rocks and ores of carbonatite complexes in the Urals are associated with orogenic and post-collision settings.